The write to well-being: a mixed methods case study integrating SEL into academic content through journaling to promote adolescent well-being - Hodges Bellinger, Kristin (Kansas State University, 2024)
Adolescents today need mental health support (U.S. Department of Health and Human Services, 2024), and schools are a place where a universal approach to positive well-being can be promoted (Weissberg, 2019). While programs exist for social and emotional learning (SEL), there is a call for teachers to find a way for daily SEL integration into the classroom context (Frey et al., 2019). This dissertation explores the idea of using journaling to link SEL to academic content for potential improvements in well-being. Research on SEL is expanded by adding a method for integration by classroom teachers through the writing process that organically links social-emotional competencies to academic learning and situations. The findings from three studies highlight the advantages for fifth grade students from writing and reflecting upon SEL topics in different content classrooms. Increases in student life satisfaction ratings and themes found during student interviews, such as the acts of journaling creating positive emotions and teaching students about themselves, suggest that students gained holistically from the experience.
Keywords: Writing; Adolescence; Social and emotional learning; Well-being; Middle school